Description of selected diagnostic tools in assessing the risk of venous thromboembolic disease - Piotrkowska, Renata; Jarzynkowski, Piotr; Książek, Janina (Nursing in the 21st Century, 2016)
DESCRIPTION OF SELECTED DIAGNOSTIC TOOLS IN ASSESSING THE RISK OF VENOUS THROMBOEMBOLIC DISEASEIntroduction. Deep vein thrombosis (DVT) and its most severe complication, pulmonary embolism (PE) is an interdisciplinary medical problem. Despite a wealth of knowledge, pulmonary embolism is the cause of about 10% of deaths among hospitalized patients and the most common factor which can be prevented. Therefore correct, rapid diagnosis of the patient’s assessment of the risk of sudden death and the quick implementation of treatment are essential to reduce mortality in this disease and prevent its distant complications.Aim of the study. The aim of this paper is to discuss on the basis of Polish and world literature the selected diagnostic tools in assessing the risk of venous thromboembolic disease.